The Role of Damage-Associated Molecular Patterns (DAMPs) in Human Diseases : Part II: DAMPs as diagnostics, prognostics and therapeutics in clinical medicine - Walter G. Land (Sultan Qaboos University Medical Journal, 2015)
This article is the second part of a review that addresses the role of damage-associated molecular patterns (DAMPs) in human diseases by presenting examples of traumatic (systemic inflammatory response syndrome), cardiovascular (myocardial infarction), metabolic (type 2 diabetes mellitus), neurodegenerative (Alzheimer’s disease), malignant and infectious diseases. Various DAMPs are involved in the pathogenesis of all these diseases as they activate innate immune machineries including the unfolded protein response and inflammasomes. These subsequently promote sterile autoinflammation accompanied, at least in part, by subsequent adaptive autoimmune processes. This review article discusses the future role of DAMPs in routine practical medicine by highlighting the possibility of harnessing and deploying DAMPs either as biomarkers for the appropriate diagnosis and prognosis of diseases, as therapeutics in the treatment of tumours or as vaccine adjuncts for the prophylaxis of infections. In addition, this article examines the potential for developing strategies aimed at mitigating DAMPs-mediated hyperinflammatory responses, such as those seen in systemic inflammatory response syndrome associated with multiple organ failure.